Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/978-1-4939-3628-1_22
|View full text |Cite
|
Sign up to set email alerts
|

Models of Oxygen Induced Retinopathy in Rodents

Abstract: Much of the knowledge we have gained into the development of pathological ocular angiogenesis has come from the development of in vivo models that enable functional assessment of key components of signaling pathways in disease progression. Indeed, rodent models have facilitated identification of several therapeutics that target pathological angiogenesis. Two of the most widely used rodent models of oxygen induced retinopathy (OIR), Smith's mouse model and Penn's rat model reproducibly induce neovascularization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…ERG analyses revealed that, while WT and BMCMC-injected mast cell–deficient mice had complete loss of b-waves and oscillatory potential–waves (OP-waves), mast cell–deficient mice injected with saline had normal b- and OP-waves, comparable to those of naive WT mice ( Figure 2F and Table 2 ). Because there are some differences between the mouse and rat OIR models ( 30 ), we also performed experiments using mast cell–deficient Kit Ws/Ws rats ( 31 ). The results of the rat model were in keeping with those of the murine model ( Figure 3 and Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…ERG analyses revealed that, while WT and BMCMC-injected mast cell–deficient mice had complete loss of b-waves and oscillatory potential–waves (OP-waves), mast cell–deficient mice injected with saline had normal b- and OP-waves, comparable to those of naive WT mice ( Figure 2F and Table 2 ). Because there are some differences between the mouse and rat OIR models ( 30 ), we also performed experiments using mast cell–deficient Kit Ws/Ws rats ( 31 ). The results of the rat model were in keeping with those of the murine model ( Figure 3 and Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this model, mouse pups are exposed to a hyperoxic environment consisting of 75% oxygen from postnatal day 7 (P7) until postnatal day 12 (P12). This hyperoxic treatment causes the regression of capillary blood vessels at the central retina in the mouse pups. Upon return to normal room air oxygen (i.e., normoxia) at P12, the central avascular retina experiences hypoxia, leading to the proliferation of endothelial cells from existing blood vessels that may lead to neovascularization. ,, Studies have demonstrated that the hypoxia-inducible factor-1α (HIF-1α) plays a central role in the pathogenesis of neovascularization. Thus, there has been a focus on developing therapies that stabilize HIF-1α as a means to protect capillary blood vessel from high-oxygen-induced vascular regression and thus protect from subsequent hypoxia-derived neovascularization . However, the contribution of bone-marrow-derived activated monocytes to neovascularization remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…15 Male gender contributes to severe ROP. 15 Models for oxygen-induced retinopathy exist, 16 although the duration of mechanical ventilation seems to be a greater predictive factor for ROP development than the total duration of oxygen supplementation. 17 Previous studies indicate that plasma proteins can be useful in identifying preterm newborn infants at high risk for developing diseases such as bronchopulmonary dysplasia, respiratory distress syndrome, and persistent ductus arteriosus.…”
Section: Introductionmentioning
confidence: 99%